Anti-dumping and countervailing procedures use or abuse? : implications for developing countries (New York United Nations, 2001)
Analyzes antidumping and countervailing duty investigations, particularly as they impact developing countries. This study also scrutinizes WTO agreements and finds that many of the negative effects of antidumping and countervailing measures are not ad equately addressed.
"Sales No. E.01.II.D.6"--T.p. verso.
"UNCTAD/ITCD/TAB/10"--T.p. verso.
At head of title: United Nations Conference on Trade and Development.
Includes bibliographical references (p. 29-31).
Keywords: World Trade Organization; Antidumping duties; Dumping (International trade)